Response of the ammonia oxidation activity of microorganisms in surface sediment to a controlled sub-seabed release of CO2. (July 2015) - Watanabe, Yuji; Tait, Karen; Gregory, Simon; Hayashi, Masatoshi; Shimamoto, Akifumi; Taylor, Peter; Stahl, Henrik; Green, Kay; Yoshinaga, Ikuo; Suwa, Yuichi; Kita, Jun
Highlights: The impact of an artificial sub-seabed CO2 leakage on benthic ammonia oxidation was examined. Potential ammonia oxidation was not inhibited by CO2 leakage. Natural seasonal variability influenced amoA gene and transcript abundance. Abstract: The impact of a sub-seabed CO2 leak from geological sequestration on the microbial process of ammonia oxidation was investigated in the field. Sediment samples were taken before, during and after a controlled sub-seabed CO2 leak at four zones differing in proximity to the CO2 source (epicentre, and 25 m, 75 m, and 450 m distant). The impact of CO2 release on benthic microbial ATP levels was compared to ammonia oxidation rates and the abundance of bacterial and archaeal ammonia amoA genes and transcripts, and also to the abundance of nitrite oxidizer ( nirS ) and anammox hydrazine oxidoreductase ( hzo ) genes and transcripts. The major factor influencing measurements was seasonal: only minor differences were detected at the zones impacted by CO2 (epicentre and 25 m distant). This included a small increase to ammonia oxidation after 37 days of CO2 release which was linked to an increase in ammonia availability as a result of mineral dissolution. A CO2 leak on the scale used within this study (<1 tonne day −1 ) would have very little impact to ammonia oxidation within coastal sediments. However, seawater containing 5% CO2 did reduce rates of ammonia oxidation. This was linked to the buffering capacity of the sediment, suggesting that the impact of a sub-seabed leak of stored CO2 on ammonia oxidation would be dependent on both the scale of the CO2 release and sediment type.